THE ELEMENTS OF TORT IN TURKISH LAW - Ay, Yunus Emre (Indonesia Private Law Review, 2024)
According to the Turkish Code of Obligations, one of the sources of obligation is tort. A tort is the damage caused to another person by an unlawful act of a negligent person with a causal link. As can be understood from the definition of tort, the elements of tort are unlawful act, damage, fault and causal link. The elements of tort are not defined in the Turkish Code of Obligations, but are defined by the authors in the doctrine. There is no prior contractual relationship between the parties to the tort. A legal relationship arises between the parties after the tort is committed. The emergence of this legal relationship depends on the realization of the elements of tort. Therefore, in this study, in order to better understand the concept of tort, definitions of the elements of tort shall be made and the contents of the elements of tort shall be explained in the Turkish Code of Obligations. After the definitions are made in the light of the doctrine, the elements of the tort shall be discussed with examples by referring to various sources. Thus, a study shall be conducted for a better understanding of the concept of tort. In this study, doctrinal research method shall be used to analyze the current legislation since it has been the most influential and dominant research method in the field of law in the past and present. It is concerned with the methodical search, analysis, explanation, and justification of the legal framework. This paper is also concerned with methodical search, analysis, explanation, and justification of the Turkish Code of Obligation which regulates tort law provisions. Primary and secondary sources are enjoyed and library based research is conducted. In this way, the provisions of the Turkish Code of Obligation which regulates the tort law shall be discussed in the light of the doctrinal discussion.